The Prevalence and Related Factors of Anterior Open Bite in Dental Patients of the Lower Northern Part of Thailand - Sasigornwong, Udom; Samnieng, Patcharaphol; Satrawaha, Sirichom (Asian Health, Science and Technology Reports, 2018)
The aim of this study was to determine the prevalence of anterior open bite and interpret its related factors. A cross-sectional study was carried out in 400 dental patients (169 males, 231 females, ages from 4 years, mean age 31 + 21.9 years) who attended dental hospital, Naresuan university. The presence of anterior open bite and other factors was collected with clinical examination and history taking by one trained dentist. Ninety one patients (25.7%) presented anterior open bite. The patients aged 4-18 years presented the most prevalence compared with others. Logistic regression showed tongue-thrust swallowing and non-nutritive sucking were significantly related to anterior open bite with Odd ratio = 2.5 (1.302-5.933) and 3.5 (1.429-8.411) respectively. For relationship between anterior open bite and other types of malocclusion, we found spacing of maxillary incisors and large overjet were significantly related to anterior open bite with Odd ratio = 5.6 (2.093-14.929) and 1.6 (1.121-2.453) respectively. In conclusion, dental patients of the lower northern part of Thailand presented a high prevalence of anterior open bite which related to certain types of malocclusion and abnormal oral habits. Dentist should realize this high prevalence and emphasize the management of anterior open bite and its related factor which could be the main problem in dental treatment procedure.